Nutritional strategies in ruminant feeding - Succi G.; Crovetto G.M. (Feed manufacturing in the Mediterranean region: Recent advances in research and technology, 1999)
The main mechanisms involved in N excretion and CH4 emission by ruminants are briefly summarized. While the contribution of ruminants to the global warming effect through CH4 emission seems to be exaggerated, this is not the case for N pollution: there is an urgent need for a reduction of N excretion into the environment and animal nutritionists and farmers must be aware of this. Diets fed to dairy cows or beef cattle should contain the minimum N content, but all the fermentable energy needed to maximize rumen microbial protein synthesis. Additional single rumen protected amino acids can be satisfactorily included in low protein diets to meet metabolic amino acid requirements. Forages (preferably of medium N and high energy content) and other home-grown feedstuffs are increasingly used on cattle farms. In Italy, diets for dairy and beef cattle in the most intensive areas are mainly based on maize silage as the principal forage component and maize grain (dry or wet) as the energy concentrate supplement. The quantitative and qualitative differences between maize silage as the first, and only crop in the year and maize silage as a second crop after Italian ryegrass or a winter cereal are discussed. The results of some studies on dietary N reduction in lactating cows and some typical diets fed in Northern Italy are also reported and commented upon.
2. Conference of Feed Manufacturers of the Mediterranean, 1998/03/25-27, Reus (Spain)